Pengaruh Iklim Organisasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Perpustakaan Dan Arsip Kabupaten Tapanuli Tengah - Frans Haryono Sitompul; Mansur Tanjung; Hendra Syahputra (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to examine the effect of organizational climate and job satisfaction on employee performance at the Library and Archives Office of Central Tapanuli Regency. The research method used is descriptive correlational, with a population and sample of 30 employees (saturated sampling). Data were collected using questionnaires that had been tested for validity and reliability. Data analysis techniques included classical assumption tests (normality, heteroscedasticity, and multicollinearity), correlation analysis, coefficient of determination, multiple linear regression, and hypothesis testing (t-test and F-test). The results show a positive relationship between organizational climate and employee performance with a correlation coefficient of 0.366 (low category), and a positive relationship between job satisfaction and employee performance with a coefficient of 0.243 (low category). The regression equation obtained is Y = 4.004 + 0.471X1 + 0.414X2. The t-test results indicate that organizational climate has a positive and significant effect on employee performance (t-value 2.543 > t-table 2.04841; sig 0.017 < 0.05), while job satisfaction has a positive but not significant effect (t-value 1.949 < t-table 2.04841; sig 0.062 > 0.05). The coefficient of determination shows that organizational climate and job satisfaction contribute 24.1% to employee performance, while the remaining 75.9% is influenced by other variables outside this study. Simultaneously, the F-test indicates that organizational climate and job satisfaction have a significant effect on employee performance.